2018
DOI: 10.1002/joc.5728
|View full text |Cite
|
Sign up to set email alerts
|

On the reduction of trend errors by the ANOVA joint correction scheme used in homogenization of climate station records

Abstract: correction method, which is expected to be the most accurate published method. We find that, if all 7 breaks are known, this method produce unbiased trend estimates and that in this case the 8 uncertainty in the trend estimates is not determined by the variance of the inhomogeneities, but by 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…All of the four methods will be examined for a medium‐sized station network and two of the four will also be examined with a denser station network. Note that although the final purpose of homogenization is not the break detection but the removal of non‐climatic biases from the observed data, the break detection is an important step (Venema et al ., 2012; Lindau and Venema, 2013, 2016), and break detection errors may seriously affect the final accuracy of homogenization products (Lindau and Venema, 2018a). Note also that in homogenization tasks including the exhaustive analysis of station history, the skill of break detection may have a large and direct impact on the accuracy of the homogenization results.…”
Section: Introductionmentioning
confidence: 99%
“…All of the four methods will be examined for a medium‐sized station network and two of the four will also be examined with a denser station network. Note that although the final purpose of homogenization is not the break detection but the removal of non‐climatic biases from the observed data, the break detection is an important step (Venema et al ., 2012; Lindau and Venema, 2013, 2016), and break detection errors may seriously affect the final accuracy of homogenization products (Lindau and Venema, 2018a). Note also that in homogenization tasks including the exhaustive analysis of station history, the skill of break detection may have a large and direct impact on the accuracy of the homogenization results.…”
Section: Introductionmentioning
confidence: 99%
“…The variance of an RD process is in principle equal to σ δ 2 , the variance of the random numbers used to create the segment levels. In this estimation, we neglect the slightly increased effective variance due to the assumed different lengths of the segments, which are caused by the stochastic occurrence of the breaks (Lindau and Venema, ). Nevertheless, the jump heights between two levels consist of the sum of two of such independent random numbers so that their variance σ β 2 is twice as large. VarRD0.25em=0.25emσδ2=σβ22. …”
Section: The Different Characteristics Of Brownian Motion and Random mentioning
confidence: 99%
“…Even more important are the different effects, the two breaks types will have on the trend. Lindau and Venema () investigated the trend introduced by RD breaks. Assuming zero mean jump sizes, they found that the error variance of the trend decreases with the number of breaks.…”
Section: The Different Characteristics Of Brownian Motion and Random mentioning
confidence: 99%
“…The variance of an RD process is in principle equal to V G 2 , the variance of the random numbers used to create the segment levels. In this estimation we neglect the slightly increased effective variance due to the assumed different lengths of the segments, which are caused by the stochastic occurrence of the breaks (Lindau and Venema, 2018b). Nevertheless, the jump heights between two levels consist of the sum of two of such independent random numbers so that their variance V E 2 is twice as large.…”
Section: The Different Characteristics Of Brownian Motion and Random mentioning
confidence: 99%